Contribution of agriculture sector to national economy in Nepal - Adhikari, Santosh (Journal of Agriculture and Environment, 2015)
Agriculture is the mainstay of majority of Nepalese people which provides employment, foods and shelter. However, the investment in agriculture in not encouraging, received only about 3 percent of total government outlays during 2002 to 2014. In the study, Gross Domestic Product was regressed with Domestic Savings, Government Expenditure on Agriculture and Foreign Direct Investment on Agriculture with the data from FY 2002/03 to 2014/15. Regression reveals the degree of association among these variables is significant at 5 % level of significance (R=0.991, P=0.005